2016
DOI: 10.1902/jop.2016.160204
|View full text |Cite
|
Sign up to set email alerts
|

Low Social Position, Periodontal Disease, and Poor Oral Health‐Related Quality of Life in Adults With Systemic Arterial Hypertension

Abstract: Short title: periodontitis, quality of life and hypertension Conflict of InterestThe authors declare that there are no conflicts of interest in this study.A one-sentence summary describing the key finding(s) Periodontal disease predicted poor OHRQoL and mediated the link between smoking, socioeconomic status and OHRQoL in people with systemic arterial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 50 publications
4
26
0
7
Order By: Relevance
“…The result of the association between oral clinical conditions and OHRQoL is consistent with previous research in children, adolescents and adults. For example, Foster Page reported a direct relationship between malocclusion and poor OHRQoL in adolescents, and that OHRQoL was indirectly predicted by dental caries experience.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The result of the association between oral clinical conditions and OHRQoL is consistent with previous research in children, adolescents and adults. For example, Foster Page reported a direct relationship between malocclusion and poor OHRQoL in adolescents, and that OHRQoL was indirectly predicted by dental caries experience.…”
Section: Discussionsupporting
confidence: 88%
“…The identification of predictors of OHRQoL has been considered a relevant topic in dental research. Poor clinical oral health status, demographic characteristics, psychosocial factors and socioeconomic conditions have been identified as predictors of OHRQoL in different age groups [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Previous studies involving children and adolescents have reported the potentially harmful influences of dental caries, dental trauma, missing teeth, gingivitis and malocclusion on OHRQoL 6,7,[9][10][11][12]14,15,[20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiologic data support that periodontitis is associated with a higher prevalence of arterial hypertension 10–13 . Unfortunately, previous evidence of an association between periodontitis and BP has been derived from small intervention studies 14 , 15 and cross‐sectional studies, 16 , 17 in which no causal link can be established. Therefore, one of the great difficulties with the linkage between periodontitis and hypertension is the so‐called “chicken and egg phenomenon.” 11 , 18 , 19 In patients diagnosed with refractory hypertension and generalized chronic periodontitis, it has been reported that together with antihypertensive management, periodontal treatment may further reduce BP levels 14 .…”
mentioning
confidence: 99%
“…Another possible limitation is that the impact of patient perception in the 4‐week postoperative period on long‐term changes in QoL was not considered. In addition, previous study revealed that adverse relationships have been shown among socioeconomic status, smoking, and periodontal status on OHRQoL [26]. In our study, we removed the smoking factor.…”
Section: Discussionmentioning
confidence: 93%